Petrażycki w sprawie Bejlisa - Cywiński, Zbigniew (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The subject of this paper is to introduce a lesser-known article that Leon Petrażycki published in 1913 into a broader context. Said article was written in response to the then-famous trial of Menahem Beilis, a Kievan Jew accused of ritual murder. The introduction of the paper briefly covers the context of the Beilis case, referring both to the trial itself as well as the social tensions surrounding it that illustrate the state of social communication in contemporary Russia and civil society institutions in statu nascendi. Special attention was paid to the reasons for which Petrażycki involved himself in the issues that divided the citizens of a multinational and multicultural Russian Empire. Primary importance was assigned to Petrażycki’s ethics, which he openly declared and which were expressed both in his civic work and in his legal theory. They are expressed, for example, in the belief that values law is based on have fundamental meaning for legal policy science – the science of planned social change, which has as a goal approaching the ideal of universal love, realised by impressing on the legal emotions of individuals. Furthermore, the article points out possible motivations that come from the same basis but are tied to Petrażycki’s social and political engagements. The fundamental issue was opposing antisemitism as a particularly severe form of cultural discrimination. Fighting antisemitism, which societies and Eastern and Central Europe were often accused of, was obvious to anyone involved in supporting reforms introduced in the occidental spirit of freedom and equality. Furthermore, other possible sources were indicated, especially the effort to weaken the accusations of antisemitism levied upon Poles under the Russian rule. The article points out that although Petrażycki’s work has elements of an opinion piece, and does not even shy from ad personam arguments, its worth is proven not by its social engagement, but also the scientific content, couched in journalistic style but entrenched in Petrażycki’s theory, which shows the possibilities created by psychological legal theory. In particular, the text focuses on the possibilities of using said theory in empirical analysis and critique of social normativity. Petrażycki’s reflections upon the nature of social norms, especially those that can be placed in a broad understanding of law and those that show possibilities of empirical study of their social influence, are worth bringing to attention. The fundamental intent of this article is proving that Petrażycki, although very critical of the sociology he knew and who only marginally brought up the possibility of empirical study of law, in fact was open to methods of studying law that could be called socio-legal, and that there is no conflict between an introspection-based theory of legal experiences and a possibility for an empirical study of legal behaviour, both of groups and individuals. In this sense, the paper shows Petrażycki as a sociologist of law.